(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objectives: The purpose of this study was to isolate and identify microorganisms of food packaging papers of Kathmandu valley and determine antibiotic susceptibility of the isolates. Methods: A total of 34 food packaging paper samples were collected aseptically from hotels, bakeries and sweet shops (considered as closed shop) and open street vendors and were transported to microbiology laboratory of Golden Gate International College for processing. The isolates were identified by standard microbiological procedures and subjected to antimicrobial susceptibility testing by modified Kirby-Bauer disk diffusion method following CLSI guidelines. The rate of Extended Spectrum Beta- lactamase (ESBL) producing and multiple drug resistant (MDR) isolates were also determined. Results: All 34 samples yielded microbial growth with average microbial count of 4.145×105 CFU/g. Among 103 microbial isolates, 78 were bacteria, 15 molds and 10 yeasts. The predominant bacterial and mold isolates were Bacillus spp (43.59%) and Cladosporium spp (46.67%) respectively. Ciprofloxacin (42/43) and Amikacin (42/43) were the most effective and ampicillin (39/43) was most resistant antibiotics for Gram negative bacteria. A total of 9.30% Gram negative isolates were identified as ESBL producing and MDR strains. Conclusion: This result indicates that potential pathogens are found in food packaging papers which can be threat to health of consumers as they may act as a source of food borne infection.